Interactions between fiscal policy and real economy in the Czech Republic a quantitative analysis - Valenta, Vilém (2011)
After many decades, macroeconomic effects of fiscal policy have returned to the centre of the economic policy debate. Both automatic fiscal stabilizers and discretionary fiscal stimuli have been used to support aggregate demand during the recent global economic crisis with a subsequent need for large-scale fiscal consolidations. In this context, a proper assessment of the size of automatic fiscal stabilizers and fiscal multipliers represents a key input for fiscal policymaking. This dissertation provides a quantitative analysis of the interactions between fiscal policy and real economy in the Czech Republic. The impact of real economy developments on public finances is assessed based on the methods of the OECD, the European Commission and the ESCB for the identification of general government structural balances, i.e. balances adjusted for effects of the economic cycle and net of one-off and other temporary transactions. I find that the underlying fiscal position, as approximated by the government structural balance, was mostly below the level stabilising the debt-to-GDP ratio since mid-1990s. An indistinct improvement in the structural balance can be identified in the period 2004--2007, which was subsequently reversed by the adverse structural impact of the world economic crisis. At the same time, dynamics of unadjusted fiscal balance was largely determined by one-off transactions in the past. The effects of fiscal policy on real economy are analysed using the structural VAR approach. I find that an increase in government spending has a temporary positive effect on output that peaks after one to two years with a multiplier of around 0.6. Tax multiplier appears to be small and, in contrast to standard Keynesian assumptions, positive. Government spending is supportive to private consumption, contradicting the hypothesis of Ricardian equivalence, but it crowds out private investment in the short run.